Factors affecting well-being among retired older adults: A protocol for an umbrella review - Yasin M. Yasin; Areej Al-Hamad; Kateryna Metersky; Emily Read; Richelle Witherspoon (PLoS ONE, 2026)
Background As global populations age, retirement has emerged as a critical life transition influencing well-being across physical, mental, social, financial, and spiritual domains. Although numerous systematic reviews have examined aspects of well-being in retirement, the evidence remains fragmented, with limited integration across domains. No umbrella review has comprehensively synthesized determinants and interventions influencing multidimensional well-being among retired older adults. Methods This protocol describes an umbrella review that will synthesize evidence from systematic reviews examining factors and policy, programmatic, community-based, or other supportive efforts associated with physical, mental, social, financial, and spiritual well-being among retired older adults. The review follows Joanna Briggs Institute (JBI) methodology for umbrella reviews and is reported in accordance with PRISMA-P guidance. The search strategy was developed in consultation with a knowledge synthesis librarian and peer reviewed using the PRESS guidelines. Database searches were conducted in MEDLINE (Ovid), CINAHL, PsycINFO, Scopus, and the Cochrane Database of Systematic Reviews for articles published from 2015 onward. Backward and forward citation searching will be undertaken. Two reviewers will independently screen records, extract data, and appraise methodological quality using the JBI Critical Appraisal Checklist for Systematic Reviews and Research Syntheses. Findings will be synthesized narratively. This protocol has been registered with PROSPERO (CRD420251158970). Discussion This umbrella review will provide an integrated, high-level synthesis of existing evidence on well-being in retirement, informing future research, policy, and practice aimed at supporting holistic and equitable aging.